العلاقة بين الاستثمار الأجنبي المباشر والنمو الاقتصادي: دراسة حالة الجزائر للفترة "1970 - 2013" باستخدام نموذج متجه تصحيح الخطأ "VECM" - جلولي، نسيمة; صوار، يوسف (جمعية إدارة الاعمال العربية, 2015)
This paper attempts to investigate the relationship between foreign direct investment (FDD and economic growth (GDP) of Algeria for the period (1970-2013), our empirical investigation follows three step procedure, we begin bv testing for non- stationarity in the two variables FDI and GDP using Augmented Dickey Fuller to determine the order of integration of the variables, the results show that the two variables are integrated of same order. Then we use the test of Johansen-Juselius to obtain the number of co-integration in the second step of our estimation. Given the evidence of co-integration in the long-run among FDI and GDP we use vector error correction model to check whether there exists causality between them, our finding study shows that FDI has a negative impact in the long-run and short- run on GDP and statistically significant, this finding may be interpreted as evidence that there is uni¬directional causality from FDI to GDP.
تحاول هذه الدراسة البحث في العلاقة بين الاستثمار الأجنبي المباشر والنمو الاقتصادي بالجزائر للفترة (1970- 2013)، باتباع مجموعة من الاختبارات الإحصائية، بداية من اختبار استقرارية السلاسل الزمنية لـ ديكى فولار المطور ADF لتحديد رتبة التكامل بين السلسلتين، وبعد التأكد من استقرار السلسلتين من نفس الرتبة تم إجراء اختبار التكامل المشترك لـ Johansen-Juselius في المرحلة الثانية للحصول على عدد متجهات التكامل، ليتم في المرحلة الأخيرة تقدير نموذج متجه تصحيح الخطأ VECM لتحديد اتجاه العلاقة السببية بين المتغيرين، وخلصت النتائج إلى أنه توجد علاقة سببية سلبية معنوية إحصائياً في المدى الطويل والمدى القصير تتجه من الاستثمار الأجنبي المباشر إلى النمو الاقتصادي، بمعنى الاستثمار الأجنبي المباشر يؤثر سلباً على النمو الاقتصادي للجزائر.
Keywords: الاقتصاد الجزائري -- النمو الاقتصادي -- الاستثمار الأجنبي المباشر -- نموذج متجه تصحيح الخطأ